Characteristics and mechanisms of long-lasting 2021–2022 summer Northeast Pacific warm blobs - Chen, Jiajie; Li, Ronglin; Xie, Shen; Wei, Jiaqi; Shi, Jian (Frontiers in Marine Science, 2023)
Warm blobs are persistently warmer-than-normal seawaters over the Northeast Pacific (NEP), which cause substantial impacts on marine ecosystems and climate. Recently, the warm blobs occurred consecutively in spring and summer of 2021 and 2022. The warm blob in 2021 was mostly located east of 155°W, while it shifted to west of 155°W in 2022. Based on a mixed-layer heat budget analysis, we find that atmospheric processes positively and dominantly contributed in May 2021 and July 2022. Specifically, less latent heat loss from the ocean caused by reducing background westerlies and evaporation intensified the 2021 warm blob, while more shortwave radiation heating due to decreased low clouds intensified the one in 2022. However, the positive contribution of the atmospheric processes cannot maintain a season due to their strong internal variability. The seasonal persistence of the warm blobs, instead, is owing to the offset between the atmospheric and oceanic processes. We highlight the importance of atmospheric processes in the evolution of the NEP warm blobs in spring and summer, which lacks sufficient investigation but can provide more potential predictability for the NEP warm blobs.